PENDEKATAN DEEP LEARNING DALAM PENDIDIKAN: STRATEGI MEMPERKUAT IDENTITAS BUDAYA - Prasetyo, Okhaifi; Rahman, Aulia; Supiyah (LP2M Universitas Muslim Nusantara Al Washliyah, 2025)
Cultural identity is the distinctive characteristics, values, and collective expressions that distinguish a group of people. However, globalization has not only facilitated the exchange of information but also eroded the boundaries of cultural identity. History lessons, which should be a bulwark of cultural identity, are instead considered boring by students. Therefore, this study aims to analyze the strategy of a deep learning approach in high school history teaching to strengthen cultural identity. This study employed library methods with a descriptive, qualitative approach, utilizing both primary and secondary data sources. The results show that the deep learning approach in history teaching emphasizes the principles of mindful, meaningful, and enjoyable learning experiences. By integrating the eight dimensions of the graduate profile, this approach yields a comprehensive learning framework that aligns with current demands. One of the primary strategies for implementing deep learning is through problem-based projects and the use of technology, which encourage students to engage in solving real-life problems. This approach not only encourages students to memorize historical facts but also to understand, apply, and reflect on historical knowledge in their daily lives. Overall, deep learning in history teaching at the high school level has great potential to strengthen cultural identity.